4, 5‐Bis(diphenylthiophosphinoyl)‐1, 2, 3‐triazolate interaction with gold nanoparticles and flat surfaces to form self‐assembled monolayers. (25th June 2020) - Correa‐Ascencio, Marisol; Galván‐Miranda, Elizabeth K.; García‐Montalvo, Verónica; Cao, Roberto; Cea‐Olivares, Raymundo; Jiménez‐Sandoval, Omar; Vera‐Estrada, Irma Lucía
Abstract : The interaction of the 4, 5‐bis(diphenylthiophosphinoyl)‐1, 2, 3‐triazolate (SPTz − ) with different gold surfaces was investigated (nanoparticles, an electrode, and flat sheets). Studies on binding affinity of this dithiophosphin‐triazolate on a gold electrode were performed by cyclic voltammetry (CV). Voltammograms exhibit two reductive desorption and only one oxidative readsorption, indicating that once reabsorbed, the molecule achieves a unique conformation. The morphology and average size of modified gold nanoparticles were studied by transmission electron microscopy (TEM) (av. diameter of 5.9 ± 1.8 nm). Further characterization was made by UV‐visible (UV‐vis) spectroscopy showing surface plasmon resonance (SPR) at about 580 nm. The bonding configurations of SPTz − on gold have also been investigated by comparing the FT‐IR and FT‐Raman spectra. The 31 P{ 1 H} NMR spectrum of capped nanoparticles exhibited two sharp signals at 30.3 and 29.6 ppm and a very broad signal at 72.7 ppm. X‐ray photoelectron spectroscopy (XPS) showed SPTz − can accomplish a strong interaction with gold nanoparticles through bonds involving a sulfur atom and a nitrogen from the triazole ring with a free terminal PS group, forming self‐assembled monolayers (SAM). This may allow subsequent functionalization through free S/N atoms of the formed SAMs. The SPTz − packing led to a reduction in packing density that permits large spaces between adsorbed headgroups and the inclusion of carbon and oxygen impurities from small molecules; nevertheless, oxidized sulfur or nitrogen species were not detected, indicating the chemical stability of the obtained SAMs.